DERMATOSE PUSTULAR SUBCORNEAL DE SNEDDON-WILKINSON - João Costelha; Artur Barros (Sociedade Galega de Medicina Interna, 2020)
Subcorneal pustular dermatosis is a rare, chronic, relapsing pustular eruption that strikes the corneal layer of the skin and presents with a neutrophilic infiltrate on histopathological examination. It was first described by Sneddon and Wilkinson in 1956 and affects mainly middle-aged and elderly women. Its coalescing vesiculopustular eruptions typically involve the flexion sites of the trunk and proximal extremities Its etiology is unknown, but pathophysiological mechanisms are related to an increased tumor necrosis factor-α. It is frequently related to systemic pathologies, particularly hematological (gamopathies, multiple myeloma) and inflammatory diseases (rheumatoid arthritis). The picture is illustrative of a clinical case of an IgA Gamopathy. The diagnosis of dermatosis is established if the classic signal is present (see picture), or a confirmatory histology. Disease without cure, dermatological control´s treatment and prognosis is dependent on systemic associations.